MAINSTREAMING HIV AND AIDS: ASSESSING STRATEGIC DIRECTION AT UGANDA MANAGEMENT INSTITUTE - Mwanga , Elizabeth Jane (Top Journal of Public Policy and Administration (TJPPA), 2024)
This study explores the integration of HIV and AIDS mainstreaming within the strategic direction of the Uganda Management Institute (UMI). Despite global emphasis on incorporating HIV and AIDS issues into development strategies, and similar efforts within the higher education sector, UMI's approach to this integration has been limited. Utilizing a mixed-methods approach that combines cross-sectional and case study research designs, the study employed interviews, Focus Group Discussions (FGDs), and document reviews. A two-level narrative analysis was conducted to uncover patterns and themes in participants' experiences and stories. Findings reveal that HIV and AIDS were minimally incorporated into UMI's strategic plans and monitoring activities. The research highlights the need to overhaul the mainstreaming model to better align with UMI’s core mandate, incorporating relevant structures and systems. The study concludes that strategic plans and policies alone are insufficient; effective HIV and AIDS mainstreaming requires a comprehensive approach including structural adjustments and resource allocation. Recommendations include a thorough analysis of HIV and AIDS issues and the development of mitigation measures during strategic and annual planning processes to facilitate effective planning, budgeting, implementation, and monitoring